Optimizing Wnt-3a and R-spondin1 concentrations for stem cell renewal and differentiation in intestinal organoids using a gradient-forming microdevice1. Issue 91 (9th October 2015) - Ahmad, Asad A.; Wang, Yuli; Sims, Christopher E.; Magness, Scott T.; Allbritton, Nancy L.
<x xml:space="preserve">Abstract</x> A gradient-generating device assayed the impact of Wnt-3a and R-spondin1 on colonoids identifying concentrations required to yield a physiologically-relevant epithelium.